Advance care planning documentation strategies; goals‐of‐care as an alternative to not‐for‐resuscitation in medical and oncology patients. A pre–post controlled study on quantifiable outcomes. Issue 12 (5th December 2018) - Morgan, David J. R.; Eng, Derek; Higgs, Dominic; Beilin, Maria; Bulsara, Caroline; Wong, Milly; Angus, Louise; Waldron, Nicholas
Abstract: Background: Health services in Tasmania, Victoria and now Western Australia are changing to goals‐of‐care (GOC) advance care planning (ACP) documentation strategies. Aim: To compare the clinical impact of two different health department‐sanctioned ACP documentation strategies. Methods: A non‐blinded, pre–post, controlled study over two corresponding 6‐month periods in 2016 and 2017 comparing the current discretional not‐for‐resuscitation (NFR) with a new, inclusive GOC strategy in two medical/oncology wards at a large private hospital. Main outcomes were the uptake of ACP forms per hospitalisation and the timing between hospital admission, ACP form completion and in‐patient death. Secondary outcomes included utilisation of the rapid response team (RRT), palliative and critical care services. Results: In total, 650 NFR and 653 GOC patients underwent 1885 admissions (mean Charlson Comorbidity Index = 3.7). GOC patients had a higher uptake of ACP documentation (346 vs 150 ACP forms per 1000 admissions, P < 0.0001) and a higher proportion of ACP forms completed within the first 48 h of admission (58 vs 39%, P = 0.0002) but a higher incidence of altering the initial ACP level of care ( P = 0.003). All other measures, including ACP documentation within 48 h of death ( P = 0.50), activation of RRT ( P = 0.73) and admission to critical ( P = 0.62) or palliative ( P = 0.81) care services, remained similar. GOC documentation was often incomplete, with most sub‐sections left blank between 74 and 87% of occasions. Conclusion: Despite an increased uptake of the GOC form, overall use remained low, written completion was poor, and most quantitative outcomes remained statistically unchanged. Further research is required before a wider GOC implementation can be supported in Australia's healthcare systems.